Review on Maintainable, Efficient & Reliable IoT Middleware for Critical Applications - Kirti Singh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The necessity of the IoT Middleware in critical applications cannot be overstated. Middleware plays a pivotal role in military operations, healthcare delivery, robotics, and farming, where seamless integration of IoT devices is crucial. As a conduit between devices and applications, it ensures real-time data transmission, enhances security protocols and facilitates interoperability across heterogeneous networks and platforms. This functionality is paramount in critical settings, where timely and accurate information can indicate the difference between success and failure. Through the utilization of IoT Middleware, these applications achieve heightened situational awareness, precise data analytics, and context-aware communication, thereby revolutionizing operational strategies and decision-making processes. Research conducted on IoT Middleware has led to remarkable achievements, including improved scalability, enhanced security measures, and seamless integration with existing infrastructure. As a result, critical applications across diverse domains have witnessed significant advancements in operational efficiency, resource optimization, and overall effectiveness, ultimately leading to better outcomes in military missions, patient care delivery, robotic automation, and precision agriculture.